PREFERENSI DAN PERMINTAAN KONSUMEN RUMAH TANGGA TERHADAP BIHUN TAPIOKA DI KECAMATAN PURBOLINGGO KABUPATEN LAMPUNG TIMUR - Ayu Vidyaningrum; Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research’s aims to determine the preferences, demand pattern and the factors which affect households demand for tapioca vermicelli in District of Purbolinggo of East Lampung Regency. This research was conducted by survey method. The research location is determined on purpose which is in District of Purbolinggo East Lampung Regency. This research was conducted in the markets and stalls around the house in District of Purbolinggo. There were 60 respondents household vermicelli tapioca in this study that was taken by accidental sampling. The data collection was carried out in June-September 2015. The method of analysis used in this study was quantitative descriptive to determine the preferences of households against tapioca vermicelli and the method with multiple linear regression method was used to determine the factors which affected households’ demand for tapioca vermicelli in District of Purbolinggo. The results showed that consumer preferences of households in the district of Purbolinggo against tapioca noodles are in the like category. The average purchase tapioca noodles was as much as 1.36 kg/month/household, the average frequency of purchase tapioca noodles was twice in a month, tapioca vermicelli widely used by domestic consumers as a soup, as well as the brand more preferred and purchased by domestic consumers are brand Moroseneng, consumers prefer or choose where to buy tapioca vermicelli that is in the shop , both at home and at stalls around the market. The demand vermicelli tapioca by consumer households in the District Purbolinggo East Lampung regency is influenced by the price of tapioca vermicelli, noodles prices, income, number or family members, ethnicity, primary school education and secondary education. Key words: demand, preferences,tapioca vermicelli This research’s aims  to determine the preferences, demand pattern and the factors which affect households demand for tapioca vermicelli in District of Purbolinggo of East Lampung Regency.  This research was conducted by survey method.  The research location is determined on purpose which is in District of Purbolinggo East Lampung Regency. This research was conducted in the markets and stalls around the house in District of Purbolinggo. There were 60 respondents household vermicelli tapioca in this study that was taken by accidental sampling. The data collection was carried out in June-September 2015. The method of analysis used in this study was quantitative descriptive to determine the preferences of households against tapioca vermicelli and the method with multiple linear regression method was used to determine the factors which affected households’ demand for tapioca vermicelli in District of Purbolinggo.   The results showed that consumer preferences of households in the district of Purbolinggo against tapioca noodles are in the like category.  The average purchase tapioca noodles was as much as 1.36 kg/month/household, the average frequency of purchase tapioca noodles was twice in a month, tapioca vermicelli widely used by domestic consumers as a soup, as well as the brand more preferred and purchased by domestic consumers are brand Moroseneng, consumers prefer or choose where to buy tapioca vermicelli that is in the shop , both at home and at stalls around the market. The demand vermicelli tapioca by consumer households in the District Purbolinggo East Lampung regency is influenced by the price of tapioca vermicelli, noodles prices, income, number or family members, ethnicity, primary school education and secondary education. Key words: demand, preferences,tapioca vermicelli